Alternative Income Concepts and Relative Performance Evaluations: A Reply. - Kratchman, Stanley H.; Malcom, Robert E.; Twark, Richard D. (The Accounting Review, 1976)
The "Comment and Extension" of R. Picur and J. McKeown (hereafter, P and M) examines three aspects of "Alternative Income Concepts and Relative Performance Evaluations" (hereafter, KMT). The differences with P and M per their respective classifications is noted with respect to theoretical, methodological and statistical terms. The statistical extension of P and M, in particular, is completely invalid. The form of current value reporting used in KMT was shown to have theoretical support both in academia and in the profession. It does not agree with the proposal of P and M. However, the purpose was not at all to advocate a specific current value form, but to consider whether a typical current value form would indicate a performance difference among firms in an industry as compared to a typical historical cost form. The P and M proposed adjustment of liabilities to reflect changing market rates clearly would change the performance measures of the sample of KMT. However, there is no general agreement that liabilities should be so adjusted in current value financial statements, any more than there is general agreement that annuity depreciation should be used for historical cost reports.